(untitled) (Medical Forum Monthly, 2021)
ABSTRACT Objective: To evaluate the effect of educational interventions on knowledge, and family functioning of parents regarding the epileptic patient’s management. Study Design: Qausi experimental study Place and Duration of Study: This study was conducted at the Department of Neurology Faculty of Allied Health Sciences, The University of Lahore from June 2021 from October 2021. Materials and Methods: 36 parents of epileptic patients were enrolled. The parents of epileptic patients who visited in the neurology clinic (OPD) were included and the parents who were already in the health profession and whose children without seizures in the last year were excluded. Family functioning was assessed by using the Family Assessment Device (FAD). Results: Majority of patients were more than 35 years old (63.9%), females (66.7%), have secondary education (36.1%) and belongs to rural area (58.1%). After intervention it was observed a statistical significant difference in domain of FAD like problem solving, Defining Roles, Affective involvement, behavior Control and general function of family (P<0.05). Conclusion: The nurse plays a vital role in improving the family functioning of epileptic family’s. They are the key essentials for training parents. The Nursing intervention has positive impact on the family functioning of epileptic patients especially in problem solving, defining roles, affective involvement, behavior control and general function of family.